Improving Student Motivation and Learning Outcomes in Islamic Education Learning by Using the Discovery Learning Model at SD Negeri Lhok Keutapang - Furqan; Rio Rahmat (MANDAILING GLOBAL EDUKASIA, 2025)
This research aims to improve student motivation and learning outcomes in Islamic Religious Education (PAI) subjects, especially the material of My Obligatory Prayer, through the application of the Discovery Learning learning model. The background of this research is the low learning outcomes of grade III students of SD Negeri Lhok Keutapang who have not met the Minimum Completeness Criteria (KKM). The research uses the Classroom Action Research (PTK) method which is carried out in two cycles, with stages of planning, implementation, observation, and reflection. The subjects of the study were all grade III students totaling 18 people. Data was collected using learning outcome tests, teacher and student activity observation sheets, and documentation. The results of the study showed a significant increase in both the motivation aspect and student learning outcomes. In the pre-cycle, only 6 students (33.3%) achieved KKM, with an average score of 62. After the implementation of Discovery Learning in cycle I, the average score increased to 72 with a completeness of 61.1%. In the second cycle, student learning outcomes increased again with an average score of 83 and completeness reached 88.9%. This improvement shows that the use of the Discovery Learning model is effective in motivating students to be active in the learning process as well as improving understanding of the concept of prayer material. These findings confirm the importance of using innovative learning models to improve the quality of religious education in primary schools.